The Caliphate at war: the ideological, organisational and military innovations of Islamic State - Hashim, Ahmed (ProQuest Ebook Central, 2018)
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- 1. Understanding the "Islamic State" -- 2. "The Unlucky Country": A Historical and Political Survey of Iraq -- 3. "Why They Fight": Ideology and Goals -- 4. From Network to Organization: The Structure of the Islamic State and Its Predecessors -- 5. "Organizing to Fight": The Evolution of the Jihadist Way of War in Iraq -- 6. Organizing to Build Caliphate 3.0: State-Formation and Nation-Building under the Islamic State -- Conclusions -- Notes -- Index